Characterization of Agarwood distil water based on different time interval: article - Abdullah, Nurul Nadia; Ku Hamid, Ku Halim (2018)
Agarwood distil water or known as hydrosol is obtained by using hydrodistillation method. Agarwood distil water is widely used in medicine since it contains high anti-oxidant and antibacterial properties that will improve the human health. The aim of this study is to analyze the characterization of Agarwood distil water from Aquilaria malaccensis at different time interval by using Fourier Transforms Infrared (FTIR) spectroscopy and Gas Chromatography-Mass Spectrometer (GC-MS) and also to make water quality test by using Inductive Couple Plasma (ICP). The functional groups has been successful identified which there were presence of same functional groups for each hydrosols samples at different time interval such as alcohol group, alkene group, alkyne group and also aromatic ring alkane group. It showed that the different time interval did not affect the functional groups. Then, there were about 48 chemical compounds of hydrosol have been successful identified and the different chemical compounds were found for the different time interval. In this work, 1,2,4,5-Tetrazine, 1,4-diethylhexahydro was the main compound found in hydrosol. Lastly, all the samples of these hydrosols did not contain any heavy metals and safe to be used as medical treatment. In conclusion, the hydrosol from hydrodistillation process contains 1,2,4,5-Tetrazine, 1,4-diethylhexahydro which is potentially used is the treatment of diarrhoea and worm infections, and also used to treat the involuntary movements (chorea) of Huntington’s disease or progressive brain disorder that causes uncontrolled movements, emotional problems, and loss of thinking ability.